PEMODELAN STRATEGI MANAJEMEN ENERGI BERBASIS SOLUSI ANALITIS UNTUK KENDARAAN HIBRIDA LISTRIK-HIDROGEN - Dodu, A.Y. Erwin (FORISTEK : Forum Teknik Elektro dan Teknologi Informasi, 2012)
Abstract - Energy Management Strategy (EMS) implemented in the fuel cell hybrid propulsion system aims to minimize the fuel consumption needed to provide the required power demand. Various EMS methods have been built to solve the optimization problem in minimizing the fuel consumption. This paper provides a modeling of new alternative approach of EMS method calLED analytical solution which is based on the minimization of the losses in the vehicle propulsion system. This method ensures that the minimization in the propulsion losses matches the minimization in the fuel consumption. Since the minimization is applied to the propulsion losses, this method has shifted the EMS objective to minimize the losses in the fuel cell hybrid propulsion system, still enabling to supply the demanded power for traction. The important advantage of this method is that it enables the real time implementation.Keywords: Energy Management Strategy, analytical solution, Fuel Cell Hybrid Electric Vehicle.